Παπατσώνης και Δάντης - Γαραντούδης, Ευριπίδης (Σύγκριση/Comparaison/Comparison, 2020)
The object of the study is the relationship of T.K. Papatsonis with Dante’s work, and in particular with Commedia, a relationship that can be considered as crucial to understanding Papatsonis’s work, as it develops in throughout his spiritual life. In particular, are examined two thematic axes of this relationship which at certain points intersect, since they relate to creative aspects of the same intellectual. The first axis is that of Papatsonis as a poet who discourses with Dante, the second is that of Papatsonis as an essayist who praises/interprets Commedia’s Dante. The examination of the first axis focuses on the poem “Beata Beatrix” (1920). The second part of the study describes and comments on the eight essays on Dante written by Papatsonis from 1915 to 1965.